Prevalens, pengetahuan, sikap dan amalan serta faktor risiko berlebihan berat badan di kalangan penduduk Kampung Sesapan Batu Rembau, Hulu Langat - Mahasiswa/wi Perubatan Fasa 2, Kumpulan 3 Sesi 1998/99 (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 1999)
Overweight (OBW) is an increasing health problem in Malaysia. A cross sectional study was conducted amongst the population of Kampung Sesapan Batu Rembau,aged 18 years and above to study the prevalence, knowledge, attitude and practice towards overweight and its risk factors. Respondents were selected using simple random sampling. Height (m) and weight (kg) of respondents were measured with the net benefit of RM 19.7 million. If both parameters were fixed at 50%, the benefit to cost ratio will go up to 3.27 with the net benefit of RM 36.6 million. In conclusion, the benefit of mass Hib immunisation outweigh the cost and hence it is a worthwhile programme to be implemented in this country.using standard methods. The guided questionnaires by trained interviewer was used to acquire information on socioeconomic and risk factors. Majority of respondents were women (60.7%). The prevalence of OBW amongst the population was 47.3%.There was a significant relationship between sex and OBW of which 53.9% of women respondent were OBW as compared to men which was only 37.3% (p< 0.05). By age, 48.0% of respondent aged 22-54 years old were OBW. Biological factor such as family history of OBW had a significant association with overweight (p< 0.05). In term of education, respondents who had primary school education level were found to have higher prevalence (53.4%) of OBW compared to those who had no formal education (48.5%) or higher educational level (39.3%). By physical activity, 50.0% respondents who performed heavy physical activity were OBW, followed by moderate (48.0%) and light (40.0%). Eventhough 57.7% of respondents have knowledge on OBW 49.4% of them were overweight. Study also showed that 53.5% of the positive attitude group were overweight compared to the negative attitude group (36.7%). The similar pattern is also seen in the practice score of which although having a good practice 48.5% of them were overweight as compared to 44.9% from the poor practice group.